2022
DOI: 10.1167/iovs.63.1.18
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Sublayer Analysis of Human Retinal Inner Plexiform Layer Obtained by Visible-Light Optical Coherence Tomography

Abstract: Purpose Growing evidence suggests that dendrite retraction or degeneration in a subpopulation of the retinal ganglion cells (RGCs) may precede detectable soma abnormalities and RGC death in glaucoma. Visualization of the lamellar structure of the inner plexiform layer (IPL) could advance clinical management and fundamental understanding of glaucoma. We investigated whether visible-light optical coherence tomography (vis-OCT) could detect the difference in the IPL sublayer thicknesses between small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…Registration and averaging of multiple volumes have allowed the visualization of single cells, and the concept of Vis-OCT fibergraphy (Vis-OCTF) of imaging-specific retinal ganglion cell (RGC) axon bundles has been introduced in animal models (108)(109)(110). Ultrahigh resolution Vis-OCT (UHR Vis-OCT) is capable of imaging sublayers within retinal layers, such as the IPL (Figure 2), and improvements in the axial resolution have also been made using rapid spectral shaping, axial tracking, and in vivo spatially dependent numerical dispersion compensation (111)(112)(113). Zhang et al have also developed a circumlimbal scanning method to image the anterior segment, capable of visualizing the Schlemm canal and the limbal microvascular network (114).…”
Section: Visible Light Optical Coherence Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Registration and averaging of multiple volumes have allowed the visualization of single cells, and the concept of Vis-OCT fibergraphy (Vis-OCTF) of imaging-specific retinal ganglion cell (RGC) axon bundles has been introduced in animal models (108)(109)(110). Ultrahigh resolution Vis-OCT (UHR Vis-OCT) is capable of imaging sublayers within retinal layers, such as the IPL (Figure 2), and improvements in the axial resolution have also been made using rapid spectral shaping, axial tracking, and in vivo spatially dependent numerical dispersion compensation (111)(112)(113). Zhang et al have also developed a circumlimbal scanning method to image the anterior segment, capable of visualizing the Schlemm canal and the limbal microvascular network (114).…”
Section: Visible Light Optical Coherence Tomographymentioning
confidence: 99%
“…(G) A depth-resolved line profile of the glaucoma eye IPL sublayers. This figure was reprinted from Ghassabi et al ( 113 ) with permission under a Creative Commons Attribution 4.0 International License.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Although the signal source is underappreciated, it was postulated that the slow inner retinal IOS might be associated with an integral effect of electrophysiological signal transduction between multiple inner retinal neurons, such as bipolar cells, amacrine cells, horizontal cells, and ganglion cells. The plexiform layer in the retina consists of a complex synaptic network containing numerous dendrites from different types of neurons ( 76 , 77 ). Their synaptic signaling might affect optical signal properties.…”
Section: Org Interpretations and Its Challengesmentioning
confidence: 99%
“…Die zunehmend höhere Auflösung der Gewebsdarstellung mit der OCT bietet Chancen, Biomarker zu verbessern oder spezifischer zu machen. Ghassabi et al [23] OCT-Aufnahmen mitentstehen, und konnten so mit einer Genauigkeit von 96 % Glaukome mit einer mittleren RNFL-Restdicke von 62 µm richtig klassifizieren.…”
Section: Statische Oct-biomarker Als Progressionsbiomarkerunclassified
“…Increases in tissue resolution with OCT provide opportunities to improve biomarkers or render them more specific. Ghassabi et al [23] reported results for retinal visualization using an experimental vis-OCT (visible light OCT) with an axial resolution of 1.8 µm in the tissue. It was possible to present the IPL in three sublayers, whereby middle layer thickness varied significantly from normal in moderately advanced glaucomas by 14.4 µm to 17.2 µm.…”
Section: How Can Presentation Of Static-structuralmentioning
confidence: 99%